Metaphors across models: On the interpretation and use of metaphors in qualitative research - Paul J. Ilecki (Adult Education Research Conference, 1996)
A conceptual framework that indicates how researchers interpret informants’ metaphoric speech, how informants themselves use and understand their own metaphors, and even how metaphors represent "truth" are the often assumed but missing pieces of qualitative research. This paper constitutes research on qualitative research methods in four disciplines: education/adult education, anthropology, psychology and theology. Those results are applied to a review of how informant metaphors are interpreted and used in examples of qualitative research in the four selected research models. The paper concludes with the assertion that researchers should be more forthcoming with the assumptions that determine how they interpret and use informants’ metaphors. When metaphors are analyzed in light of these assumptions, a consistent understanding may govern the presentation of findings and conclusions.